THE DEVELOPMENT OF TEACHING MODULE OF DATABASE APLICATION BY USING SQ3R LEARNING MODEL FOR GRADE X STUDENTS OF SOFTWARE ENGINEERING AT SMK NEGERI 1 NEGARA - Prita Nugrahini, Ni Putu (Universitas Pendidikan Ganesha, 2012)
This study aimed at (1) designing and implementing the development of teaching modules of database application by using SQ3R learning model for grade X students of Software Engineering at SMK Negeri 1 Negara; (2) analyzing students’ response toward the development of teaching modules of database application by using SQ3R learning model for grade X students of Software Engineering at SMK Negeri 1 Negara. The development of this teaching module is done by seeing problem in the field where the students’ understanding toward the materials are less because they are slow to catch and understand the concept of learning materials, moreover the reference book that the students have is very limited.This research is a Research and Development by using SQ3R (Survey, Question, Read, Recite, Review) or called by scanning method. This research was done up to stage of development and analyse the students’ respon toward developed teaching module. Model development used refers to the model of Dick and Carrey Model development. Teaching modules which have been developed will be testes by students of grade X of Software Engineering at SMK Negeri 1 Negara in order to know the students’ respon. The population of this research is grade X students of Software Engineering at SMK Negeri 1 Negara and the study sample is grade X RPL 2 with the number of students are 35 students. Based on the results of the percentage of student responses to the development of teaching modules of Database Applications can be categorized as very positive. Very positive response indicates that the students are happy and motivated in learning by using teaching module. This is because of this teaching module contains pictures for being discussed, material with clear and organized steps, summary and exercises to measure students’ understanding of the material that has been explained and there is the review at the end of the module after studying the six chapters, in which the students summarize the whole material of the sixth chapters on the sheet that has been provided. So that students have better understanding and comprehending about the content material of Database Applications